Band-pass filters application in quantitative and qualitative interpretation of gravimagnetic anomalies; Проблемы геологии и освоения недр; Т. 2 - Tengelid D. I. (Geology, mining and petroleum engineering (English, German), 2012)
Заглавие с титульного листа